Tribological Behavior of Functional Surface: Models and Methods - Pawlus, Pawel; Dzierwa, Andrzej (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Material loss due to wear and corrosion and high resistance to motion generate high costs. Therefore, minimizing friction and wear is a problem of great importance. This book is focused on the tribological behavior of functional surfaces. It contains information regarding the improvement of tribological properties of sliding elements via changes in surface topography. Tribological impacts of surface texturing depending on the creation of dimples on co-acting surfaces are also discussed. The effects of various coatings on the minimization of friction and wear and corrosion resistance are also studied. Friction can be also reduced by introducing a new oil.